IM4ON: instructional materials for Office environment/ Naliza Solat ... [et al.] - Solat, Naliza; Salim, Azmi; Nik Min, Nik Mohd Faris; Ammar, Muhammad; Ishak, Haidar; Abdullah, Mohd Zulkifli; Abdullah, Nasiha (2023)
Instructional material plays a crucial role in the learning process because it can promote active engagement and help the instructors and students meet their goals effectively. Currently, the students’ exposure to the elements of the office environment in the OBM345 course is limited, as they primarily learn theoretical concepts in class. In March 2023, a survey of students’ perceptions of the elements of the office environment was conducted among 106 students from the UiTM Pahang, UiTM Kelantan, and UiTM Terengganu campuses. The lack of interesting instructional materials hinders the students’ ability to grasp the theoretical knowledge, thus impacting their preparedness for real-world work scenarios. Many students also struggle to comprehend and memorise technical terms and complex theories. Besides, the subtopics in this chapter lack updates on the latest trends, resulting in an incomplete understanding of the subject’s matter. Inadequate instructional materials and the use of PowerPoint slides pose barriers to students mastering the chapter content, thus highlighting the need for improved resources. The findings of the survey indicated that students expressed a preference for various enhancements in teaching and learning pertaining to the subjects. They also expressed a desire for engaging instructional materials and interesting resources. Therefore, IM4ON is recommended to assist instructors and students in mastering this topic. The idea of integrating all pertinent details on one platform offers effective strategies for delivering the content and enables the students to have a better learning experience.